2002
DOI: 10.1084/jem.20020620
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 21 Is a T Helper (Th) Cell 2 Cytokine that Specifically Inhibits the Differentiation of Naive Th Cells into Interferon γ–producing Th1 Cells

Abstract: The cytokine potential of developing T helper (Th) cells is directly shaped both positively and negatively by the cytokines expressed by the effector Th cell subsets. Here we find that the recently identified cytokine, interleukin (IL)-21, is preferentially expressed by Th2 cells when compared with Th1 cells generated in vitro and in vivo. Exposure of naive Th precursors to IL-21 inhibits interferon (IFN)-γ production from developing Th1 cells. The repression of IFN-γ production is specific in that the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
209
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(223 citation statements)
references
References 40 publications
11
209
3
Order By: Relevance
“…Accordingly, IL-2 and IL-15 induced expansion of CD27 Ϫ virus-specific T cells, whereas IL-21 promoted outgrowth of CD27 ϩ cells. Although both IL-2 and IL-21 are helper cell-derived cytokines, the differentiation of CMV-specific memory CD8 ϩ T cells to a CD27 Ϫ phenotype upon activation with whole CMV-Ag in combination with peptide shows that the role of IL-21 production by CMV-specific CD4 ϩ memory T cells, reported to have a Th1 profile (42), is limited in accordance with previous reports in which IL-21 was shown to be a Th2 cytokine (43). Whereas production of helper cell-derived cytokines as IL-21 and IL-2 is limited to the antigenic activation phase, IL-15 can be produced by a number of lymphoid and nonlymphoid cells (44).…”
Section: Discussionsupporting
confidence: 32%
“…Accordingly, IL-2 and IL-15 induced expansion of CD27 Ϫ virus-specific T cells, whereas IL-21 promoted outgrowth of CD27 ϩ cells. Although both IL-2 and IL-21 are helper cell-derived cytokines, the differentiation of CMV-specific memory CD8 ϩ T cells to a CD27 Ϫ phenotype upon activation with whole CMV-Ag in combination with peptide shows that the role of IL-21 production by CMV-specific CD4 ϩ memory T cells, reported to have a Th1 profile (42), is limited in accordance with previous reports in which IL-21 was shown to be a Th2 cytokine (43). Whereas production of helper cell-derived cytokines as IL-21 and IL-2 is limited to the antigenic activation phase, IL-15 can be produced by a number of lymphoid and nonlymphoid cells (44).…”
Section: Discussionsupporting
confidence: 32%
“…A recent study showed that IL-21 inhibited IFN-g production from developing Th1 cells and could serve to amplify the Th2 responses. 10 Since the biological outcome of IL-21-induced responses could depend on the cellular context of the IL-21 signals, 10 NK cell-mediated responses induced by IL-21 may be differently modulated by the presence of IL-23. Human pancreatic cancer is susceptible to immunocompetent cells 21 and possible vaccination using gene-modified cancer cells has been clinically examined.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, contradictory results were also reported; IL-21 is secreted from Th2 cells and inhibits the development of interferon-g (IFN-g)-producing Th1 cells. 10 IL-23 is composed of the p19 subunit, which is a novel molecule related to the p35 subunit of IL-12, and the p40 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively or additionally, it is possible, given our data, that IL-21 production by activated CD4 T cells could play a role in down-modulating IFN-␥ secretion by CD8 T cells at the site of secondary challenge with Ag. Evidence exists to indicate that both Th1 and Th2 cells can produce IL-21 (35,(55)(56)(57). Because activated CD4 Th1 cells are already secreting copious quantities of IFN-␥, this may provide a mechanism for the avoidance of cytokine storm repercussions.…”
Section: Discussionmentioning
confidence: 99%